Limited‐Transpiration Trait May Increase Maize Drought Tolerance in the US Corn Belt. (1st November 2015) - Messina, Carlos D.; Sinclair, Thomas R.; Hammer, Graeme L.; Curan, Dian; Thompson, Jason; Oler, Zac; Gho, Carla; Cooper, Mark
Abstract : Yield loss due to water deficit is ubiquitous in maize ( Zea mays L.) production environments in the United States. The impact of water deficits on yield depends on the cropping system management and physiological characteristics of the hybrid. Genotypic diversity among maize hybrids in the transpiration response to vapor pressure deficit (VPD) indicates that a limited‐transpiration trait may contribute to improved drought tolerance and yield in maize. By limiting transpiration at VPD above a VPD threshold, this trait can increase both daily transpiration efficiency and water availability for late‐season use. Reduced water use, however, may compromise yield potential. The complexity associated with genotype × environment × management interactions can be explored in a quantitative assessment using a simulation model. A simulation study was conducted to assess the likely effect of genotypic variation in limited‐transpiration rate on yield performance of maize at a regional scale in the United States. We demonstrated that the limited‐transpiration trait can result in improved maize performance in drought‐prone environments and that the impact of the trait on maize productivity varies with geography, environment type, expression of the trait, and plant density. The largest average yield increase was simulated for drought‐prone environments (135 g m −2 ), while a small yield penalty was simulated for environments where water was not limiting (–33 g m −2 ). Outcomes from this simulation study help interpret the ubiquitous nature of variation for the limited‐transpiration trait in maize germplasm and provide insights into the plausible role of the trait in past and future maize genetic improvement.